Uma análise referente a composição de gênero na dimensão de Conselho de Administração e Diretoria das empresas que compõem o Índice de Sustentabilidade Empresarial da B3 - Jonas, Ayana Aparecida Negrão de (2024)
The study aimed to evaluate how companies in the 18th portfolio of the B3 Corporate Sustainability Index align with Sustainable Development Goal (SDG) No. 5, which focuses on gender equality. Specifically, it examined female representation in the Board of Directors and Executive Board of these companies. The evaluation focused on identifying women's participation in these positions within the index's portfolio, as these companies are recognized as sustainable investment options in Brazil. This analysis is linked to ESG (Environmental, Social, and Governance) practices, crucial for business continuity, and the disclosure of diversity information in the Board's composition due to these indicators in their reports. Upon analyzing the composition of the Board of Directors and Executive Board of the selected companies, it was found that there is still a relevant gap in female participation. This outcome historically reflects the persistent gender inequalities in the country, particularly in high leadership positions where the lack of gender diversity is more pronounced, regardless of the initiatives and progress these companies may have demonstrated in this area